Synthesis and Physicochemial Properties of Three Glutaric Acid Diester - Samidin, Salma Bte (Journal of Science and Technology, 2016)
Abstract Three diesters were prepared through the esterification reaction of diacid (glutaric acid) with 3 different straight chain alcohols with para-toluene sulphonic acid (PTSA) (4%) as a catalyst. The resulting products were confirmed by Fourier Transform Infrared (FTIR) and Nuclear Magnetic Resonance (NMR) analyses. The oxidative stability, viscosity, flash point and pour point were measured.  Dioctyl glutarate and didecyl glutarate showed a liquid form at room temperature. Glutaric acid diesters produced show high oxidative stability, higher than 187ËšC and high temperature pour point. Didodecyl glutarate forms solid at room temperature and shows high flash point of 210ËšC and viscosity index VI of 194 respectively. Keywords: Biolubricant, esterification, glutaric acid, alcohol